TOLERANSI ANTAR UMAT BERAGAMA DI KELURAHAN SANTIAGO KECAMATAN TAHUNA KABUPATEN KEPULAUAN SANGIHE - Davidson Takasana; Grace Soputan; Theodorus Pangalila (JURNAL PARADIGMA : Journal of Sociology Research and Education, 2021)
The Indonesian nation is often affected by conflicts in the name of religion. In the Village of Santiago, an atmosphere of life is created in the differences between religious communities. This study uses a qualitative approach with a research focus (a) on religious days, (1) Eid, (2) Eid ketupat, (3) Easter, (4) Christmas, (b) general community activities, (1) funeral ceremonies, (2) wedding ceremony, (3) traditional tulude ceremony, and supporting factors (1) the role of government, (2) religious leaders, (3) local wisdom, along with inhibiting factors (1) economy, (2) education, (3) tribal differences. The technique of collecting data through observation, interviews and documentation, while the data analysis technique uses Grounded Theory. Research Results: (1) the people of Kelurahan Santiago apply mutual respect, a sense of togetherness, solidarity, cooperation, equality and additional combinations of galipoho and tulude cultures in being tolerant and maintaining tolerance, (2) the people of Kelurahan Santiago prioritize local culture in building interactions in social, so it is very difficult for conflict to occurn abstract consisting of 150 to 250 words with 11 points Times New Roman, 1 space and left aligned. Abstract includes research problems, research objectives, research methods, and research results.